Incidence of excess oxygen use in critically ill children and its impact on clinical outcomes: A single-center, retrospective study from Pakistan - Rubab Naz; Sahira Ahmed; Muhammad Irfan; Safa Alam; Anwarul Haque (Journal of Pediatric Critical Care)
Background: Oxygen therapy is crucial yet costly, with limited research on hyperoxemia in children, often relying on invasive PaO2 measurements. This study aims to assess the prevalence of excessive oxygen use in critically ill children using noninvasive SpO2 as a substitute for invasive arterial blood gases and explores its association to morbidity and mortality outcomes. Subjects and Methods: We conducted a retrospective study at the pediatric intensive care unit (PICU) of a tertiary care hospital in Pakistan between January 2022 and July 2023. Critically ill children between the age of 1 month and 15 years receiving oxygen therapy through high-flow nasal cannula (HFNC) or mechanical ventilation (MV) for over 24 h were studied. Cumulative excess oxygen exposure (CEOE) was quantified as the mean hourly FiO2 exceeding 0.21, while SpO2 was ≥95% during the first 24 h of ventilation and categorized into quartiles. Results: Of the 191 children, 126 (66%) were ventilated using MV, while 65 (34%) received HFNC. Common diagnoses included respiratory illnesses (48.2%), neurological disorders (18.3%), sepsis (12%), and surgical cases (10.5%). The median CEOE was 32.46 (interquartile range = 21.08–42.75). 50.3% were in higher CEOE quartiles (>32.46). No statistically significant differences were observed in multiorgan dysfunction syndrome (MODS) and mortality rates between the lower quartiles (first and second) and the higher quartiles (third and fourth). Conclusions: Fifty percent of the critically ill children were exposed to excess oxygen. There was no significant difference in the incidence of MODS and mortality across the lower and higher quartiles of CEOE.